Using “TELL ME MORE” software in teaching-learning of French for students pedagogy at the Department of Foreign Languages, Faculty of Education, National University of Laos.: https://doi.org/10.69692/SUJMRD0802274 - THAMMASALO, Olady; HATSADY, Soudachanh; DEROBERT, Olivia (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
The study aimed to self-training in the teaching-learning of French as a foreign language using the “TELL ME MORE” software the students majoring in French Pedagogy Course of Faculty of Education, National University of Laos. In our research we want to get involved to respond to the request for training support on the "TELL ME MORE" software in collaboration between the National University of Laos, the AUF association and the Francophone center. This software is installed at the Francophone Center of the National University of Laos. For teachers and students of French at the National University of Laos. The target group was the students from 3rd year, majoring in French Pedagogy Course of Faculty of Education, National University of Laos with the total number of 34 (18 females and 16 males). The research tool was the questionnaire and class observation grid. The statistics used to analyze data to find percentages using computer programs. The research results can be summarized as follows: The majority of the population prefers to use the TELL ME MORE software to develop skills in French such as: speaking (41.2%), listening (23.5%), writing (17. 6%) and reading (17.6%) meaning most students use it for speaking and listening. The activities that students use a lot in the TELL ME MORE software are pronunciation (88 %), conversation and grammar (82%), written production (73%), photo and audio, video and word writing activities (70%).